The Effect of Realistic Mathematics Education Learning Model on Students’ Triarchic Intelligence - Michael Christian Simanullang (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
This study aims to analyze the effect of the Realistic Mathematics Education (RME) learning model on students' triarchic intelligence. This study is a quasi-experiment with a pretest-posttest control design. The instruments used in this study were: (1) validation sheets; and (2) students' triarchic intelligence tests. The results of this study are: (1) the students' triarchic intelligence scores taught with the RME learning model are in the high category; (2) there is a significant difference on the students' triarchic intelligence scores taught by the RME learning model and direct learning; (3) the students' triarchic intelligence scores taught by the RME learning model is higer than the students' triarchic intelligence scores taught by direct learning; and (4) the implementation of the RME learning model can increase students' triarchic intelligence.Keywords: Quasi-Experiment, Learning Model, RME, Triarchic Intelligence